Efficacy of Solution Focused Brief Therapy on Self-concept of Bullied Adolescents - Malhotra, Richa; Suri, Sushma (International Journal of Psychosocial Rehabilitation, 2020)
The present study was conducted to investigate the efficacy of Solution-Focused Brief Therapy (SFBT) on the self-concept of bullied adolescents. The participants were students from secondary & senior secondary schools in New Delhi. A sample of 30 adolescents (14 boys & 16 girls) was selected from Grades 8 to 11 within the age bracket of 13-16 years by employing random sampling. The sample was divided into experimental and control groups using the Fishbowl technique. A pre-post test experimental design was used. The Wilcoxon signed-rank test and Mann-Whitney U-test were employed to analyze the data. The study indicated that (a) there was no significant difference between the two groups on self-concept before intervention; (b) there exists a significant difference between the experimental and control groups with respect to self-concept after intervention; (c) the effect size computed for assessing magnitude of efficacy was found to be high; and (d) significant changes were reported in the physical, social, temperamental, educational, and intellectual domains of self-concept. It was concluded that SFBT is an effective approach to enhance the self-concept of bullied adolescents.